2023
DOI: 10.32859/era.26.76.1-15
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Indigenous Ethnomedicinal knowledge of Genus Nepeta from Azad Jammu & Kashmir, Pakistan

Muhammad Manzoor,
Mushtaq Ahmad,
Muhammad Zafar
et al.

Abstract: Background: Medicinal plants have a high value to humans due to their medicinal constituents and potential biological consequences. The current study provides valuable insights into the Nepeta genus and its significant ethnobotanical worth within the rich diversity landscape of the division of Muzaffarabad.Methods: Ethnomedicinal data was gathered by using a questionnaire and the group discussion method. Group discussions were carried out in local dialect to facilitate clear communication with local population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…According to the World Health Organization (WHO), phytotherapy is the most widely used medical treatment worldwide (6). In developing countries, the utilization of plants as medicines constitutes a significant component of the healthcare system (7)(8)(9)(10). Ishtiaq and Khan (11) reported that over 80% of prescribed medicines originate from substances extracted from medicinal plants or are developed using semi-synthetic methods.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), phytotherapy is the most widely used medical treatment worldwide (6). In developing countries, the utilization of plants as medicines constitutes a significant component of the healthcare system (7)(8)(9)(10). Ishtiaq and Khan (11) reported that over 80% of prescribed medicines originate from substances extracted from medicinal plants or are developed using semi-synthetic methods.…”
Section: Introductionmentioning
confidence: 99%